Հրեաների լեզվի հայերեն անունների և դրանց տարբերակների բառարանային մշակման պատմությունը - Գյուրջինյան, Դավիթ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Армянское название еврейского языка (с неправильным написанием։ էբրաէրէն) впервые было зарегистрировано в армяно-латинском словаре Ф. Риволы (1621 г.). Словарь древнеармянского языка Мхитара Себастаци (1749 г.) является первым моноязычным словарем, где были зафиксированы вариантные названия еврейского языка հրէարեն и հրէէրէն. The printed dictionary, in which the Armenian name of the Hebrew language was registered for the first time (with a wrong spelling։ էբրաէրէն), was the Armenian-Latin dictionary by F. Rivola (1621). Old Armenian dictionary by Mkhitar Sebastatsi (1749) was the first monolingual dictionary where the different variants of the Hebrew language name (հրէարեն and հրէէրէն) were recorded.
Keywords: Բանասիրություն